2020
DOI: 10.1039/d0cp03902k
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystalline ZnO film decorated with gold nanospheres for PIERS chemical sensing

Abstract: In this paper, we report on the study of a novel type of substrate based on a highly crystalline ZnO film photo-irradiated by UV for enhancing Raman signal. This effect...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In addition, the SERS effect is also very useful for studying the surface catalytic reactions in order to know their mechanism and their intermediate species involved in these reactions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In this SERS field, an alternative section has emerged named photo-induced enhanced Raman spectroscopy (PIERS), which gives the possibility of having supplementary chemical enhancement of the Raman signal compared to conventional SERS, by employing a photo-activated semiconductor substrate [ 17 , 18 , 19 , 20 ]. This supplementary chemical enhancement is due to the presence of surface oxygen vacancies (V ) created during the pre-irradiation of the semiconductor substrate by UV light [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the SERS effect is also very useful for studying the surface catalytic reactions in order to know their mechanism and their intermediate species involved in these reactions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In this SERS field, an alternative section has emerged named photo-induced enhanced Raman spectroscopy (PIERS), which gives the possibility of having supplementary chemical enhancement of the Raman signal compared to conventional SERS, by employing a photo-activated semiconductor substrate [ 17 , 18 , 19 , 20 ]. This supplementary chemical enhancement is due to the presence of surface oxygen vacancies (V ) created during the pre-irradiation of the semiconductor substrate by UV light [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this SERS field, an alternative section has emerged named photo-induced enhanced Raman spectroscopy (PIERS), which gives the possibility of having supplementary chemical enhancement of the Raman signal compared to conventional SERS, by employing a photo-activated semiconductor substrate [ 17 , 18 , 19 , 20 ]. This supplementary chemical enhancement is due to the presence of surface oxygen vacancies (V ) created during the pre-irradiation of the semiconductor substrate by UV light [ 17 , 18 , 19 , 20 ]. In the literature, it is well-reported that UV light can allow the creation of defects/vacancies in different materials (nanostructured or not), such as metal oxides [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], silicon dioxide [ 25 , 26 ], and single-wall carbon nanotubes [ 27 ], for instance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations